Evolution of plant sucrose uptake transporters (SUTs) - Reinders, Anke; Sivitz, Alicia B.; Ward, John M. (Frontiers in Plant Science, 2012)
In angiosperms, sucrose uptake transporters (SUTs) have important functions especially in vascular tissue. Here we explore the evolutionary origins of SUTs by analysis of angiosperm SUTs and homologous transporters in a vascular early land plant, Selaginella moellendorffii, and a non-vascular plant, the bryophyte Physcomitrella patens, the charophyte algae Chlorokybus atmosphyticus, several red algae and fission yeast, Schizosaccharomyces pombe. Plant SUTs cluster into three types by phylogenetic analysis. Previous studies using angiosperms had shown that Types I and II are localized to plasma membrane while type III SUTs are associated with vacuolar membrane. SUT homologs were not found in the chlorophyte algae Chlamydomonas reinhardtii and Volvox carterii. However, the characean algae Chlorokybus atmosphyticus contains a SUT homolog (CaSUT1) and phylogenetic analysis indicated that it is basal to all other streptophyte SUTs analyzed. SUTs are present in both red algae and S. pombe but are less related to plant SUTs than CaSUT1. Both Selaginella and Physcomitrella encode type II and III SUTs suggesting that both plasma membrane and vacuolar sucrose transporter activities were present in early land plants. It is likely that SUT transporters are important for scavenging sucrose from the environment and intracellular compartments in charophyte and non-vascular plants. Type I SUTs were only found in eudicots and we conclude that they evolved from type III SUTs, possibly through loss of a vacuolar targeting sequence. Eudicots utilize type I SUTs for phloem (vascular tissue) loading while monocots use type II SUTs for phloem loading. We show that HvSUT1 from barley, a type II SUT, reverted the growth defect of the Arabidopsis atsuc2 (type I) mutant. This indicates that SUTs evolved similar (and interchangeable) phloem loading transporter capabilities independently.